Cultural Influence on Perceived Usefulness of Islamic Corporate Reporting Model - Dwi Ratmono; Fuad Mas’ud (Jurnal Akuntansi dan Auditing Indonesia, 2005)
The objective of this study is to examine the cultural influence on the per-ceived usefulness of Islamic corporate reporting model. This study attempts to un-derstand the antecedents of perceived usefulness of Islamic corporate reporting model. The Hofstede-Gray’s framework was utilized to develop research hypothesis that the lower in terms of Conservatism and Secrecy, the more likely to believe that the Islamic corporate reporting are more important than conventional accounting reporting. The hypothesis was also stated that the different background of institu-tions is expected to have an impact to the respondent’s perception on perceived use-fulness of Islamic corporate reporting model because the Islamic background insti-tutions have put more efforts than the conventional institutions in promoting Islamic values. The results showed that Power Distance was the best antecedents in explain-ing Gray’s accounting values and Uncertainty Avoidance has the positive significant effect on perceived usefulness of the Islamic corporate reporting model.Keywords:    conventional accounting, Islamic accounting, Hofstede-Gray frame-work, Islamic corporate reporting, perceived usefulness